2022
DOI: 10.1111/os.13312
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the In Situ Screw Implantation Region and Angle on the Stability of Lateral Lumbar Interbody Fusion: A Finite Element Study

Abstract: Objective: To investigate the effect of the in situ screw implantation region and angle on the stability of lateral lumbar interbody fusion (LLIF) from a biomechanical perspective.Methods: A validated L2-4 finite element (FE) model was modified for simulation. The L3-4 fused segment undergoing LLIF surgery was modeled. The area between the superior and inferior edges and the anterior and posterior edges of the vertebral body (VB) is divided into four zones by three parallel lines in coronal and horizontal plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In fact, when the screw was inserted from the middle of one side of the vertebral body and penetrated the cortex from the middle of the contralateral vertebral body, rigid tricortical fixation was formed due to the trajectory close to the endplate, which could both provide better initial stiffness under all loading conditions and provide superior protective effects on the interbody cage and screw‐bone interface under lateral‐bending conditions. The technique of tri‐cortical pedicle screw (TCPS) has been used to improve the anchoring strength in the vertebrae 37 . In practice, the technique of TCPS can be applied to enhance the grip strength of the screws and reduce the risk of CS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, when the screw was inserted from the middle of one side of the vertebral body and penetrated the cortex from the middle of the contralateral vertebral body, rigid tricortical fixation was formed due to the trajectory close to the endplate, which could both provide better initial stiffness under all loading conditions and provide superior protective effects on the interbody cage and screw‐bone interface under lateral‐bending conditions. The technique of tri‐cortical pedicle screw (TCPS) has been used to improve the anchoring strength in the vertebrae 37 . In practice, the technique of TCPS can be applied to enhance the grip strength of the screws and reduce the risk of CS.…”
Section: Discussionmentioning
confidence: 99%
“… 35 , 36 In addition, Zhu et al suggested that the screw penetrated the cortex of the opposite vertebral body, which was consistent with our usual implantation method. 37 In fact, when the screw was inserted from the middle of one side of the vertebral body and penetrated the cortex from the middle of the contralateral vertebral body, rigid tricortical fixation was formed due to the trajectory close to the endplate, which could both provide better initial stiffness under all loading conditions and provide superior protective effects on the interbody cage and screw‐bone interface under lateral‐bending conditions. The technique of tri‐cortical pedicle screw (TCPS) has been used to improve the anchoring strength in the vertebrae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation